Association between lactic acid sting test scores, self‐assessed sensitive skin scores and biophysical properties in Chinese females. (31st July 2019) - Ding, D.‐M.; Tu, Y.; Man, M.‐Q.; Wu, W.‐J.; Lu, F.‐Y.; Li, X.; Li, Y.; Yang, J.‐T.; Jin, Y.‐M.; Yang, C.‐Y.; He, L.
Abstract: Background: Lactic acid sting test (LAST) is a classical method to identify sensitive skin. However, some subjects with self‐perceived sensitive skin are negative for LAST. Objective: To determine whether LAST scores are associated with specific phenotype of sensitive skin. Methods: A total of 292 subjects with self‐perceived sensitive skin were enrolled in this study. The Sensitive Scale was used to evaluate the severity of burning, stinging, itching, tautness, erythema and scaling based on 0–10 scale scores. In addition to the assessment of LAST scores, epidermal biophysical properties were measured using an MPA system. Results: The Sensitive Scale scores of stinging, itching, tautness and scaling were significantly different between the LAST‐positive and ‐negative groups. However, burning and erythema scores did not differ between the LAST‐positive and ‐negative groups. LAST scores were positively correlated with the Sensitive Scale scores for stinging, itching, tautness and scaling, but not for burning and erythema scores. Moreover, LAST scores negatively correlated with stratum corneum hydration, but positively with transepidermal water loss (TEWL) rates. Conclusions: Lactic acid sting test scores positively correlated with TEWL rates. LAST scores could be used to identify subjects with sensitive skin characterized mainly by stinging and itching, but not those mainly by burning and erythema. Résumé: Contexte: Le test de la piqûre d'acide lactique (LAST) est une méthode classique pour identifier les peaux sensibles. Cependant, certaines personnes s'évaluant ayant une peau sensible sont négatifs au test LAST. Objectif: Déterminer si le score du LAST est associé à un phénotype spécifique de peau sensible. Méthodes: Au total, 292 personnes s'évaluant ayant une peau sensible ont été inclus dans cette étude. L'échelle de sensibilité a été utilisée pour évaluer la sévérité de la brûlure, du picotements, de la démangeaison, de la tension, de l'érythème et des desquamations basée sur une échelle de 0‐10. En plus de l'évaluation du score LAST, les propriétés biophysiques épidermiques ont été mesurées à l'aide d'un système MPA. Résultats: Les scores de l'échelle de sensibilité pour le picotement, les démangeaisons, la tension et la desquamation étaient significativement différents entre la groupe LAST positif et celle du LAST négatif. Cependant, les scores de la brûlure et de l'érythème n'étaient pas différents entre les deux groupes. Le score LAST était positivement corrélé avec les scores de l'échelle de sensibilité du picotement, des démangeaisons, de la tension et des desquamations, mais pas pour la brûlure et l'érythème. En plus, les scores LAST étaient négativement corrélés avec l'hydratation du stratum corneum, mais positivement corrélés avec le taux de perte en eau transépidermique (TEWL). Conclusions: Les scores LAST étaient corrélés positivement avec le taux de perte en eau transépidermique. Les scores LAST pourraient être utilisés pour identifier les personnes avec la peau sensible caractérisée principalement le picotement et les démangeaisons, mais pas la brûlure et l'érythème.